Parents' Perceptions and Actions on Digital Safety of Elementary School Students - Hamdan Husein Batubara; Ruruh Sarasati; Amalia Risfianti; Selfi Dewi Rahmawati (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis study explores parents' perceptions and actions in ensuring the digital safety of elementary school children in Indonesia, where internet penetration is high. This study utilized a mixed methods approach using a convergent parallel design to collect data from 219 parents of elementary school students through closed and open-ended questions presented by Google Forms. Quantitative data was analyzed using mean score and Pearson correlation, whereas quantitative data was analyzed using content and descriptive analysis. The study found that parents generally perceive digital devices and the internet as beneficial tools for enhancing children's learning, creativity, and communication, though they also recognize risks such as exposure to harmful content and cyberbullying. To optimize the benefits and mitigate risks, parents employ strategies such as supervising device use, setting time limits, and educating children about online safety and digital etiquette. These findings highlight the importance of digital literacy for parents and children and the need for collaboration among families, educators, and policymakers to create a safe digital environment for children.Keywords: digital safety, digital literacy, children online risk, parental strategies, parental viewsAbstrakPenelitian ini mengeksplorasi persepsi dan tindakan orang tua dalam memastikan keamanan digital anak-anak sekolah dasar di Indonesia, yang memiliki penetrasi internet yang tinggi. Penelitian ini menggunakan pendekatan metode campuran dengan menggunakan desain paralel konvergen untuk mengumpulkan data dari 219 orang tua murid sekolah dasar melalui pertanyaan tertutup dan terbuka yang disajikan oleh Google Forms. Data kuantitatif dianalisis menggunakan nilai rata-rata dan korelasi Pearson, sedangkan data kuantitatif dianalisis menggunakan analisis isi dan deskriptif. Hasil penelitian ini menemukan bahwa orang tua umumnya menganggap perangkat digital dan internet sebagai alat yang bermanfaat untuk meningkatkan pembelajaran, kreativitas, dan komunikasi anak-anak, meskipun mereka juga menyadari adanya risiko seperti paparan terhadap konten berbahaya dan perundungan dunia maya. Untuk mengoptimalkan manfaat dan mengurangi risikonya, orang tua menerapkan strategi seperti mengawasi penggunaan perangkat, menetapkan batas waktu, dan mengedukasi anak-anak tentang keamanan online dan etika digital. Temuan ini menyoroti pentingnya literasi digital bagi orang tua dan anak serta perlunya kolaborasi di antara keluarga, pendidik, dan pembuat kebijakan untuk menciptakan lingkungan digital yang aman bagi anak-anak.Kata Kunci: keamanan digital, literasi digital, risiko daring anak, strategi orang tua, pandangan orang tua